Sosiology of Apistemology in Kurdish Poetry - Hawkar Mamand Taha; Nawzad Waqas Saeed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
Epistemological sociology or "sociology of knowledge" as part of the science of sociology focuses on the study of social knowledge, i.e., the linguistic, cultural, religious and political knowledge common in a society at a given historical period At the same time, Social knowledge reflects on individuals' thoughts and personalities in different ways, while at the same time being reflected in their outcomes and inventions and inventions. Cognitive-literary sociology as one of the dimensions of this science broadly includes all other dimensions, since dimensions such as the sociology of linguistic, cultural, religious and political knowledge These are the knowledge that the author has derived from his local customs, traditions, historical and social times.